Screening for asymmetrically expressed genes in the left-right organizer of the zebrafish embryo - Pestana, Sara Filipa Silva (2018)
The left-right axis is established during early development in four steps. First the asymmetry is broken through the cilia movement within the left-right organizer (LRO) generating a leftward fluid flow. Second, the flow, or what it transports, is sensed by some organizer cells that produce an asymmetric signal. Such signal triggers a genetic cascade that transmits the asymmetric information from the organizer to the lateral plate mesoderm. Ultimately, leading to an organ-specific morphogenesis with visceral organs being placed in the correct side of the body plan. Two hypotheses try to explain how the fluid flow is sensed. The Chemosensation model proposes that a morphogen accumulates on the left side of the LRO where it is perceived by ciliated cells. To test this model we studied several taste sensing-related genes. We focused on gnaia, a gene encoding a G protein alpha subunit, highly expressed in the zebrafish LRO. However, we could not draw definitive conclusions, as gnaia knockdown did not produce major left-right defects. The second hypothesis, the ‘two cilia model’ is based on mechanosensation and predicts that two cilia populations have different functions in the LRO: the motile cilia generate the directional flow and the immotile cilia sense it through the Pkd1l1-Pkd2 complex. To test this hypothesis we looked for the expression patterns of possible downstream targets of Pkd2, screening for left-right asymmetries. However, we were not able to find new asymmetric genes, confirming that, so far, dand5 is still the only asymmetrically expressed gene in the LRO. The two-cilia model also raised the question of what makes these two cilia populations different. In order to try to understand if the difference between motile and immotile cilia was structural, we looked for the localization of Dnal1, a crucial dynein component of outer dynein arms. Results showed mCherry-Dnal1 is expressed in both cilia types, suggesting that LRO cilia may be structural identical.